School PrincSchool Principal Leadership And Work Environment: Driving Teacher Motivation At The Tanbihul Ghofilin Al Mustofa Sidoraharjo Kedamean Foundationipal Leadership And Work Environment: Driving Teacher Motivation At The Tanbihul Ghofilin Al Mustofa Sidoraharjo Kedamean Foundation - M.Abdul Rosyid Musthofa; Didit Darmawan (Hikamatzu | Journal of Multidisciplinary, 2024)
This study analyses the effect of principal leadership and work environment on teachers' work motivation at Tanbihul Ghofilin Al Mustofa Sidoraharjo Kedamean Foundation. This study used a quantitative approach with a cross-sectional research design. Respondents in the study involved all teachers at Tanbihul Ghofilin Al Mustofa Sidoraharjo Kedamean Foundation so that sampling was carried out by census. The data collection instrument was a questionnaire that had been previously validated and rehabilitated. The analysis tool is multiple linear regression. Effective leadership, and conducive work environment together contribute to shaping work motivation. The results showed the positive role of leadership and work environment on teachers' work motivation. This research contributes to developing educational leadership and improving teaching quality